2021
DOI: 10.1002/chem.202101171
|View full text |Cite
|
Sign up to set email alerts
|

Design and Application of Mini‐libraries of miRNA Probes for an Efficient and Versatile miRNA‐mRNA Cross‐linking

Abstract: MicroRNAs constitute a class of endogenous, non‐coding RNAs that influence various processes within the cell. By base‐pairing to partially‐complementary sites located in the 3’ untranslated region of target messenger RNAs, microRNAs participate in post‐transcriptional regulation of the majority of human protein‐coding genes. Their dysregulation has been related to many pathological processes and diseases. Thus, an in‐depth understanding of the microRNA mechanisms of action is crucial. Here, we present a new co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It has been reported that cross-linkers modifying the base of nucleotides are positioned in the major groove, while those modifying the ribose are positioned in the minor groove of a miRNA−target duplex. 25 Considering that the modified diazirine at C-9 of the phenoxazine nucleoside is positioned in the major groove, we wanted to compare differences in the impact of cross-linker position in the major groove versus the minor groove on photo-cross-linking efficiency. For this purpose, we tethered different diazirines (R 2 and R 3 ) to the 2′-O-position of phenoxazine nucleoside ribose (structure 3 in Scheme 1C) using a 1,2,3-triazole linker.…”
Section: ■ Resultsmentioning
confidence: 99%
“…It has been reported that cross-linkers modifying the base of nucleotides are positioned in the major groove, while those modifying the ribose are positioned in the minor groove of a miRNA−target duplex. 25 Considering that the modified diazirine at C-9 of the phenoxazine nucleoside is positioned in the major groove, we wanted to compare differences in the impact of cross-linker position in the major groove versus the minor groove on photo-cross-linking efficiency. For this purpose, we tethered different diazirines (R 2 and R 3 ) to the 2′-O-position of phenoxazine nucleoside ribose (structure 3 in Scheme 1C) using a 1,2,3-triazole linker.…”
Section: ■ Resultsmentioning
confidence: 99%
“…It is recognized that miRNAs interact with the downstream mRNAs by base pairing with mRNA 3′UTRs [Malinowska et al, 2021]. Through bioinformatic analysis and experiments, we found SETD1A was targeted by The survival fraction was determined in MKN-45 and AGS cells introduced with sh-NC, sh-FOXD2-AS1#1, or sh-FOXD2-AS1#1 + pcDNA3.1/SETD1A.…”
Section: Discussionmentioning
confidence: 95%